Efforts by the Homeroom Teacher to Address Reading Challenges Among Class III Students at SDN Bantar Kemang 06 - Muhammad Ichsan; Nurfaizah Azzahratul Husna (Mitra Palupi, 2023)
Background: The research delves into the efforts made by the class teacher to address reading challenges among third-grade students at SDN Bantar Kemang 06. While most class III students typically read proficiently, there are some in SDN Bantar Kemang 06 who require additional support in reading. Purpose: This study aims to identify the specific reading difficulties these students face and explore the teacher's strategies to overcome these challenges. Design and methods: Employing a qualitative approach, the research adopts a case study method. Data collection involves observation, interviews, and documentation techniques. The Miles Huberman Analysis Model guides data analysis through components of data reduction, presentation, and conclusion verification. To ensure data validity, triangulation methods involving source, method, and time are employed. Results: The findings reveal five key efforts by the homeroom teacher to address students' reading difficulties. Firstly, the teacher emphasizes classroom literacy. Secondly, a dedicated reading corner is established within the classroom. Thirdly, additional reading sessions of about 20 minutes are provided after regular learning activities for struggling students. Fourthly, proactive communication with parents and conducting tutoring or individual guidance sessions for students in need are implemented. The identified factors contributing to students' reading difficulties encompass intellectual, environmental, and psychological aspects. These difficulties manifest in hesitancy while reading, inadequate attention to punctuation in lengthy sentences, and a need for assistance in comprehension.